STRATEGI KEPEMIMPINAN TRANSFORMASIONAL GURU PENGGERAK DALAM MENINGKATKAN KINERJA GURU DAN KELOMPOK KERJA GURU SEKOLAH DASAR DI KECAMATAN GUNUNGPUTRI KABUPATEN BOGOR - Masitoh, Siti; Firdaus, Muhammad Yus; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to describe and analyze the transformational leadership strategies implemented by Guru Penggerak (Teacher Leaders) in improving the performance of elementary school teachers and Teacher Working Groups (Kelompok Kerja Guru / KKG) in Gunungputri District, Bogor Regency. The study is motivated by challenges in optimizing teacher performance and the role of Teacher Working Groups, which have not yet reached their maximum potential. This research employs a qualitative approach. Data were collected through in-depth interviews, observations, and documentation from various sources, including Guru Penggerak, school principals, heads of Teacher Working Groups, teacher members of KKG, and representatives from the Bogor Regency Education Office. The findings reveal that Guru Penggerak applied transformational leadership strategies through the delivery of an inspiring vision, teacher empowerment, strengthening collaboration, as well as reflective and innovative learning practices. These strategies had a positive impact on increasing teachers’ active participation in learning communities, enhancing pedagogical competence, and improving the quality of teachers’ performance in designing and implementing learning activities. The Teacher Working Group functions as a strategic forum for the sustainable professional development of teachers. This study recommends strengthening the role of Guru Penggerak in leading community-based and collaborative educational transformation. Keywords: Transformational Leadership, Motivational Teacher, Teacher Performance, Teacher Working Group, Elementary School